Traditional Sports and Games: Intercultural Dialog, Sustainability, and Empowerment - Saura, Soraia Chung; Zimmermann, Ana Cristina (Frontiers in Psychology, 2021)
From Traditional Sports and Games (TSG) we have not only learned different ways of living time as well as inhabit space and a particular mode of practicing sports and games from distinct cultures, but also promoting universal dialog among people. TSG presents sustainable and ecological references for living needed even before the advent of the COVID-19 pandemic. Nowadays, environmentally friendly policies and production methods must be taken more seriously. TSG may reveal a path to sustainable development, considering our corporeality and cultural diversity. TSG are expressions of human groups that historically reproduce their way of life-based on modes of social cooperation and specific forms of relationship with nature, traditionally characterized by sustained environmental management. The purpose of this article is to discuss how TSG promotes intercultural dialog with a focus on sustainability, and how it empowers people and creates equality among its players. We understand that TSG can break socio-cultural barriers. For this study, we considered data from a Brazilian experience of TSG’s Festival held at a public school in the city of São Paulo (Brazil), organized in collaboration with our study group. Data consists of observations recorded in pictures and films during the processes of organization, preparation, implementation, and evaluation of a TSG Festival, held in a public school in São Paulo, Brazil from the years of 2017 and 2018, with the participation of 800 students from the first to the ninth grade of elementary school, aged between 7 and 17 years. The first step in our analysis is taken from a dynamic called “Talking Circles,” where researchers registered dialog about experiences and used specific literature about TSG, from a philosophical perspective. The team and students from our study group that organized these events were invited to participate in four different Talking Circles. Approximately 20 people participated in each one of these meetings. Recurrences that emerged from these Talking Circles are presented in the results and explored afterward. What does this experience–from bodies in movement, artistic or sporting, or both–teach about intercultural dialog and empowerment? Such gestures indicate a cultural heritage and corporeal wisdom that allows humans to face new encounters and understanding in peace, recognizing humanity common to all of us, regardless of our origins. Ethical and aesthetical results of such dialog reveal possibilities to be explored in our relationship with different cultures and the environment, providing points of sustainable development through TSG.